Consumers’ Attitudes and Purchase Intention of Life Insurance in Nepal (Pravaha, 2023)
This study explores consumer attitudes and intentions to purchase life insurance in the Kathmandu Valley of Nepal. Purchase intention serves as the dependent variable, while the independent variables include tax savings, insurance agents, word-of-mouth, satisfaction, and trust. Utilizing primary data, this research aims to examine factors influencing investor behavior in the acquisition of life insurance policies.The findings of the study reveal that individuals with higher levels of education exhibit greater concern about life insurance compared to those with lower educational backgrounds.Furthermore, the results suggest that the majority of individuals are employed in the service industry rather than in government roles, as business owners, or in other fields. Life insurance policyholders showed a stronger preference for endowment policies over whole-life and term insurance. The primary motivation for purchasing life insurance is risk coverage, although people also seek it for savings, security, and peace of mind. Regression analysis indicates a strong relationship between insurance agents, decisions regarding life insurance purchases, and overall satisfaction.